Apakah Pengelolaan Keuangan Desa Sudah Akuntable? - Putri, Annie Mustika; Sari, Dian Puji Puspita (Akuntansi & Ekonomika, 2024)
The internal control system will be employed as a mediating variable in this study to examine and measure the impact of technological knowledge and equipment competency on the accountability of village finances. In this study, quantitative methodologies are applied. The research sample was village officials in the Kampar Kiri sub-district, totaling 147 respondents consisting of the village's monetary affairs department, the administrative department, the head of planning, and village secretary, the Head of Government, the Head of Welfare and Services, and BPD (Village Consultative Body). To test the hypothesis, SEM-PLS analysis with SmartPLS 4.0 software was utilized in this study. Based on the data analyzed, it is concluded that the internal control framework acts as a mediating factor between the responsibility of village financial management and the usefulness of the apparatuses and information technology use.